Fungsi Kognitif Lansia yang Beraktivitas Kognitif secara Rutin dan Tidak Rutin - Adriana Dewi Riani Djajasaputra; Magdalena S Halim (Jurnal Psikologi, 2019)
Ministry of the Health Republic of Indonesia noted that 47% of the elderly in Indonesia still work. One activity that the elderly might do is a cognitive activity, such as watching the news, reading books, art activities, and doing analytical things. Frequent cognitive activity is thought to preserve elderly cognitive function. This study aimed to see the comparison of the cognitive function of the elderly who perform a frequent and non-frequent cognitive activity. This was a quantitative study, based on 12 subtests of cognitive function as part of the Indonesian Neuropsychological Test Battery, to two elderly groups in Jakarta (N=90, 69 women and 21 men), the elderly who performed frequent and non-frequent cognitive activities. The results indicated the presence of significant cognitive functional differences in all aspects of attention, language, and memory aspects except visual reproduction subtest and verbal learning (short term) subtest, among elderly groups who performed frequent and non-frequent cognitive activities. However, there was no significant difference in cognitive function in the executive function.